2015
DOI: 10.12820/rbafs.v.20n2p152
|View full text |Cite
|
Sign up to set email alerts
|

Tendência temporal de indicadores da prática de atividade física e comportamento sedentário nas capitais da Região Nordeste do Brasil: 2006-2013

Abstract: <p class="Padro" style="margin-bottom: 0.0001pt; text-align: justify;"><span style="font-size: 12.0pt; font-family: ";Times New Roman";,serif; mso-fareast-font-family: ";Times New Roman";; color: windowtext; mso-bidi-font-weight: bold;" lang="PT">O objetivo foi analisar tendências temporais de indicadores da prática de atividade física e comportamento sedentário nas capitaisda região Nordeste entre os anos de 2006 e 2013. Foram analisados dados de 141.309 adultos (18+ anos), das nove capitais, da r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
1
1
0
9
Order By: Relevance
“…On the other hand, national studies presented similar results to the present study. Some studies in Brazil that evaluated only the habit of watching TV confirmed a decrease [16][17][18] , and Silva et al 8 and Lopes et al 9 add information that agrees with our findings, also showing a decrease in the use of TV and an increase in the use of PCs and VGs. Although these findings are opposite in some points, they approximate the findings of the present study, noting that there are clear cultural differences, as is the case with states in Brazil and developed countries; thus highlighting that these patterns may have some similarity, but are not equal.…”
supporting
confidence: 91%
“…On the other hand, national studies presented similar results to the present study. Some studies in Brazil that evaluated only the habit of watching TV confirmed a decrease [16][17][18] , and Silva et al 8 and Lopes et al 9 add information that agrees with our findings, also showing a decrease in the use of TV and an increase in the use of PCs and VGs. Although these findings are opposite in some points, they approximate the findings of the present study, noting that there are clear cultural differences, as is the case with states in Brazil and developed countries; thus highlighting that these patterns may have some similarity, but are not equal.…”
supporting
confidence: 91%
“…Observou-se, ainda, que a prática de atividade física aumentou de acordo com o grau de escolaridade dos trabalhadores. Estudo realizado nas capitais no nordeste brasileiro evidenciou que os adultos que possuíam maior escolaridade tinham mais chances de exercitar-se, enquanto os de menor escolaridade apresentaram significativa redução das chances 21 .…”
Section: Discussionunclassified
“…Frente aos fatores que estão associados à prática de atividade física de trabalhadores, pode-se considerar que ações de promoção da saúde são necessárias para essa população, as quais podem ser desenvolvidas pelas próprias empresas, tais como exercícios individuais diários, atividades de alongamento, incentivo à prática de atividades físicas coletivas no do ambiente laboral, dentre outras. Além disso, políticas governamentais tornam-se fundamentais para o incentivo das empresas e dos trabalhadores 21 . Com isso, espera-se que haja uma redução da inatividade física, dos números de DCNT e aumento na qualidade de vida e na capacidade de trabalhar desses indivíduos 5,12 .…”
Section: Discussionunclassified
“…In Portugal, the higher the educational level of adult, the longer the time spent in sedentary activities. Among Brazilians, those with higher schooling and income were more likely to being exposed to separate or simultaneous sedentary behaviors 22 . In another national study conducted in capitals of the northeastern region of Brazil with more than 140 thousand adults over 18 years of age, there was a trend of reduction in active displacement among adults with low and medium schooling 23 .…”
Section: Discussionmentioning
confidence: 99%
“…(RC: 1,61; IC95%: 1,02;2,56). Os servidores com 9 a 11 anos de escolaridade estiveram menos expostos a dois (RC: 0,27; IC95%: 0,17; 0,44), três (RC: 0,39; IC95%: 0,23; 0,66) e quatro (RC: 0,22; IC95%: 0,07; 0,69) comportamentos sedentários simultaneamente e aqueles com 12 anos ou mais de escolaridade tiveram menor chance de ter dois (RC: 0,22; IC95%: 0,10; 0,49) e três (RC: 0,15; IC95%: 0,05; 0,46) …”
unclassified